URBAN WASTE CHALLENGES AND SDG COMPLIANCE: EVALUATING MUNICIPAL SOLID WASTE MANAGEMENT IN CBC KARACHI - Syed Majid Ali Zaidi,; Sobia Sultan, (Spectrum of Engineering Sciences, 2025)
This study assesses the performance and sustainability of municipal solid waste collection in the Clifton Cantonment Board (CBC), Karachi, Pakistan, across residential, commercial, and industrial phases. Five research objectives guided the inquiry: (RO1) evaluate current collection methods—frequency, coverage, efficiency; (RO2) assess adequacy of service delivery; (RO3) identify drivers of inefficiency; (RO4) examine operational and policy challenges and discretionary improvement options; and (RO5) evaluate alignment with sustainability goals and related training needs. A mixed‑methods approach combined service log review, fleet and equipment audits, key‑informant interviews with CBC officials and contractors, GIS-supported coverage mapping, and resident surveys. Findings show highly uneven spatial and temporal coverage: densely populated residential sectors experience irregular or missed pickups, while some commercial/industrial generators receive scheduled service. Operational constraints—including an aging, poorly maintained and undersized vehicle fleet, manpower shortages, access difficulties in narrow streets, and weak route planning—undermine intended collection frequencies. Limited source segregation, low public awareness, and contamination of waste streams further reduce efficiency and recycling potential. Institutional gaps—fragmented planning, inadequate data systems, weak regulatory enforcement, and constrained financing—impede performance and hinder progress toward circular and climate-aligned waste strategies. Targeted interventions are recommended: phased fleet renewal and right‑sizing of collection equipment; digital route tracking and complaint reporting; community segregation and composting campaigns supported by incentives; structured staff training in modern handling, safety, and data reporting; strengthened bylaws with enforcement mechanisms; and a dedicated waste management fund to co‑finance infrastructure and public‑private partnerships. Improving these dimensions can reduce service inequities, divert recoverable materials, and better align CBC waste management with local sustainability objectives.